2016
DOI: 10.1007/s10157-016-1317-1
|View full text |Cite
|
Sign up to set email alerts
|

Both low and high serum ferritin levels predict mortality risk in hemodialysis patients without inflammation

Abstract: BackgroundSerum ferritin concentration >100 ng/mL was associated with a higher risk of death in hemodialysis patients in Japan, whereas such an association was less clear in hemodialysis patients in Western countries. Since Japanese dialysis patients are generally less inflamed than those in Western countries, inflammation may modify the association between serum ferritin and the adverse outcomes.MethodsWe performed an observational cohort study using data from 2606 Japanese hemodialysis patients who participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 30 publications
5
31
1
Order By: Relevance
“…While both inflammation and anemia management practices influenced ferritin levels, the relationship between high ferritin and mortality was attenuated more by adjustment for markers of inflammation than by hemoglobin levels, intravenous iron, and erythropoiesisstimulating agents doses. The recent paper also encourages the view that the association between serum ferritin and allcause mortality in HD patients is modified by inflammation (Shoji et al 2017).…”
Section: )mentioning
confidence: 62%
“…While both inflammation and anemia management practices influenced ferritin levels, the relationship between high ferritin and mortality was attenuated more by adjustment for markers of inflammation than by hemoglobin levels, intravenous iron, and erythropoiesisstimulating agents doses. The recent paper also encourages the view that the association between serum ferritin and allcause mortality in HD patients is modified by inflammation (Shoji et al 2017).…”
Section: )mentioning
confidence: 62%
“…In a study of 2,606 (mean age 64 years) patients on hemodialysis without inflammation, Shoji et al (2017) reported that both low and high ferritin levels were significantly associated with all-cause mortality (Cox proportional hazard ratios: 1.79 and 1.55 respectively). Similarly, Park et al (2015) in a prospective cohort study of 946 (mean age 60 years, range 49-70, 61% males) patients found that serum ferritin levels at the start of hemodialysis were independently associated with all-cause mortality risk, infection related and cardiovascular mortality risk (p=0.003, HR1.5, 95% CI 1.156-2.069; p=0.032, HR1.9, 95%CI 1.056-3.476 and p=0.033 HR1.6, 95%CI 1.040-2.474 respectively).…”
Section: Assessment Of Iron Status In Kidney Failure and Health Outcomementioning
confidence: 99%
“…This shift is more pronounced in older women rather than men and, at least in part, is attributed to their ceased reproductive function (no iron losses related to menstruation or pregnancy). Furthermore, elevated iron stores have been linked to exercise in the aged population (Jehn, 2004;Li et al, 2013Li et al, , 2014Shoji et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Not only iron overload but also iron deficiency and chronic anemia are associated with increased cardiovascular risk, which suggests that the relationship between iron and CVD is not linear but rather U-shaped (Shoji et al 2016). In one prospective cohort of the ARIC Study, the presence of anemia (defined as a hemoglobin concentration <130 g/l in men and <120 g/l in women) was independently associated with increased risk of CVD (HR 1.41 [95 % CI: 1.01, 1.95]) (Sarnak et al 2002).…”
Section: Lower Iron Lower Hemoglobin and Cvd Riskmentioning
confidence: 99%